Effect of slow forced eruption on the vertical levels of the interproximal bone and papilla and the width of the alveolar ridge - Kwon, Eun-Young (Korean J Orthod, 2016)
OBJECTIVE: Forced eruption has been proposed for the reconstruction of deficient bone and soft tissue. The aim of this study was to examine the changes in the alveolar ridge width and the vertical levels of the interproximal bone and papilla following forced eruption. METHODS: Patients whose hopeless maxillary anterior teeth were expected to undergo severe bone resorption and soft tissue recession upon extraction were recruited. In addition, patients whose maxillary anterior teeth required forced eruption for restoration due to tooth fracture or dental caries were included. Before and after forced eruption, the interproximal bone height was measured by radiographic analysis, and changes in the alveolar ridge width and the interproximal papilla height were measured with an acrylic stent. RESULTS: This prospective study demonstrated that the levels of the interproximal alveolar bone and papilla were significantly increased by 1.36 mm and 1.09 mm, respectively, in the vertical direction. However, the alveolar ridge width was significantly reduced by an average of 0.67 mm in the buccolingual direction. The changes in the level of the interproximal alveolar bone and papilla were positively correlated. CONCLUSIONS: Although the levels of the interproximal bone and papilla were significantly increased, the alveolar ridge width was significantly decreased following forced eruption. There was a modest positive and significant correlation between the changes in the height of the interproximal alveolar bone and the papilla. Based on our findings, modification of vertical forced eruption should be considered when augmentation of the alveolar ridge width is required.